2020
DOI: 10.1158/1078-0432.ccr-20-1310
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Biomarker Study of the Wnt Pathway Modulator DKN-01 in Combination with Gemcitabine/Cisplatin in Advanced Biliary Tract Cancer

Abstract: This study provides new insights on the effects of blocking Dickkopf-1 (DKK1), a modulator of Wnt signaling, using DKN-01. The phase I multicenter study tested the feasibility, efficacy and biological effects of DKN-01, a humanized monoclonal antibody targeting DKK1, in combination with gemcitabine and cisplatin in patients with unresectable or metastatic biliary tract cancers. The regimen was well tolerated but did not appear to have additional activity beyond historically reported efficacy with gemcitabine/c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 39 publications
(40 reference statements)
0
36
0
Order By: Relevance
“…DKK1 has not only been evaluated as a prognostic marker in a wide variety of cancers [ 9 ] but may also serve as a potential novel treatment target [ 18 ]. Recently, Goyal et al reported that DKN-01, an inhibitor of DKK-1, was well tolerable in a phase I clinical trial in combination with gemcitabine or cisplatin in patients with advanced cancer of the biliary tract [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…DKK1 has not only been evaluated as a prognostic marker in a wide variety of cancers [ 9 ] but may also serve as a potential novel treatment target [ 18 ]. Recently, Goyal et al reported that DKN-01, an inhibitor of DKK-1, was well tolerable in a phase I clinical trial in combination with gemcitabine or cisplatin in patients with advanced cancer of the biliary tract [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…DKK1 is known to inhibit Wnt signaling by interacting with the Wnt receptors of the Frizzled family 14,38 . In addition, DKK1 is associated with a so-called immune-desert microenvironment by activating myeloidderived suppressor cells and downregulating natural killer cells in cancer 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…DKK1 can inhibit Wnt signaling by interacting with the Wnt receptors of the Frizzled family 14 . DKK1 plays a role in cancer proliferation, invasion, and growth via the modulation of Wnt signaling 14,15 . DKK1 is expressed in multiple tumor types, including BTC, but its impact and the clinical role of this pathway's components are not completely understood 9,16 .…”
Section: Introductionmentioning
confidence: 99%
“…This starting dose and accelerated dose escalation were informed by a phase I monotherapy study that established safety up to DKN-01 600 mg intravenously (IV) (NCT01457417) 22 and a study confirming the safety of 150 mg and 300 mg in combination with cytotoxic chemotherapy (NCT02375880). 23…”
Section: Dkn-01 Dosingmentioning
confidence: 99%